Prevalence, subtypes, and risk factors of adverse childhood experiences among Chinese residents: a multicenter cross-sectional study - Chen, Yinhai; Lu, Yuanwei; Wen, Xiuying; Zhou, Tong; Ke, Xiong (Frontiers in Public Health, 2024)
Background Addressing the long-term physical and mental health impacts of adverse childhood experiences (ACEs) remains a significant public health challenge. Additionally, ACEs can contribute to intergenerational transmission, affecting future generations. While previous studies have primarily focused on children and adolescents, there is limited data on ACE subtypes and influencing factors among the general adult population, particularly in China. This study aims to explore the prevalence, subtypes, and factors influencing ACEs among Chinese adults. Method A total of 1,932 Chinese residents from southwest China (Sichuan, Yunnan, Guizhou provinces, and Chongqing Municipality) participated in the study, consisting of 867 men (44.9%) and 1,065 women (55.1%). Latent class analysis (LCA) was used to identify ACE clusters, and regression analysis examined associations between ACE clusters and demographic factors, physical illness, and mental health outcomes. Results The findings revealed that 28.7% of participants had experienced at least one ACE, while 13.2% had experienced three or more ACEs. Three distinct ACE clusters were identified: a low ACE group, a high emotional and physical abuse/family dysfunction group, and a high ACE/sexual abuse group. Regression analysis showed significant associations between childhood adversity and demographic factors (age, education, birthplace), as well as physical and mental health outcomes (anxiety, depression). ANOVA further confirmed significant differences in depression and anxiety scores across the clusters. Conclusion These findings offer critical insights for developing targeted public health interventions. Policymakers should consider strategies to reduce childhood ACEs and mitigate their long-term consequences, with particular attention to high-risk groups.